Technologies in a Social Context - CGIAR Initiative on Livestock and Climate; International Livestock Research Institute (International Livestock Research Institute, 2025)
The CGIAR Research Initiative on Livestock and Climate aimed to address livestock system climate adaptation and mitigation through five interrelated work packages. This series of Work Package Results Fact Sheets details our key outcome results. Work Package 1 (WP1) focused on the development, analysis and dissemination of the adaptation and mitigation dimensions of climate-smart livestock technologies. Working in Colombia, Ethiopia, Tunisia and Kenya, WP1 focused on co-developing practices with producers and characterizing socioeconomic and environmental effects. WP1 invested substantially in producer-led innovation development and scaling to strengthen knowledge exchange networks among producers, extensionists, researchers, local government and private sector actors to promote adaptive capacity.